The Effect of Investment Opportunity Set, Capital Structure, Interest Rate and Inflation on Firm Value - Muhammad Syarif Syaifuddin (Journal of Islamic Economic Scholar, 2021)
The purpose of this study is to test the influence of investment opportunity set (IOS), capital structure, interest rates and inflation on the company's values in the islamic index case studies of 2015 to 2019. It Uses the kind of quantitative research. The hypothetical testing used is the regression of the data panel using the micrsoft excells and the eviews-9 application. The sample retrieval technique USES an overwhelmingly sampling method with the number of samples as many as 13 companies. Data sources obtained from secondary data of financial statements accessed through private websites of the Indonesian stock exchange (BEI). The study shows that investment opportunity sets have a positive and significant impact on the company's values, capital structures have a positive and insignificant impact on the company's values, interest rates have a positive and insignificant impact and inflation is significantly negative and insignificant. The predictive ability of the four variables to the company's value of 56.95% and the remaining 43.5% are affected by other variables not in the research model.